The really amazing animal book - Sirett, Dawn. (New York : DK Pub., 1996)
Presents a wide variety of information on all kinds of animals.
"Based on the TV series "Amazing Animals" by DK Vision and Partridge Films"--T.p. verso.
4.2.
4.2
K-3
Keywords: Animals -- Juvenile literature; Animals -- Miscellanea -- Juvenile literature; Animals; Animals -- Miscellanea; Animals; Animals -- Miscellenea